Integrating Artificial Intelligence in Mathematics Learning to Improve Conceptual Understanding - Ahmad Hamidin; Buhari Muslim (Gema Cendekia Institute, 2026)
The rapid development of Artificial Intelligence (AI) has brought significant changes in various fields, including education. In mathematics learning, AI offers opportunities to improve students' conceptual understanding through adaptive, personalized, and data-driven learning. This article aims to examine the integration of Artificial Intelligence in mathematics learning and its contribution to improving students' conceptual understanding. The research method used is a systematic literature review of national and international journal articles relevant to the topic of AI and mathematics education. The results of the study indicate that the application of AI, such as intelligent tutoring systems, learning analytics, and educational chatbots, can help students understand mathematical concepts more deeply, reduce misconceptions, and increase learning engagement. However, AI integration also faces challenges, including teacher readiness, ethical data use, and gaps in technology access. Therefore, an appropriate implementation strategy is needed so that the use of AI in mathematics learning can be effective and sustainable.